2007
DOI: 10.1159/000112830
|View full text |Cite
|
Sign up to set email alerts
|

<i>SLC40A1</i> c.1402G→A Results in Aberrant Splicing, Ferroportin Truncation after Glycine 330, and an Autosomal Dominant Hemochromatosis Phenotype

Abstract: Background/Aims: To determine the molecular basis of a mild hemochromatosis phenotype in a man of Scottish-Irish descent. Methods: We sequenced genomic DNA to detect mutations of HFE, SLC40A1, TFR2, HAMP, and HFE2. RNA isolated from blood mononuclear cells was used to make cDNA. RT-PCR was performed to amplify ferroportin from cDNA, and amplified products were visualized by electrophoresis and sequenced. Results: The proband was heterozygous for the novel mutation c.1402G→A (predicted G468S) in exon 7 of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 66 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Apart from this type of variation, only the p.Val162 single-amino-acid in-frame deletion has been consistently associated with iron overload phenotypes. The p.Gly468Ser substitution can be considered separately, in that the underlying c.1402G>A transition disrupts the exon 7 donor site, resulting in the partial use of an exonic cryptic splice site and the generation of a truncated reading frame [27,28], while the Gly468 to Ser amino acid change by itself has no obvious effect on the ability of SLC40A1 to export iron [27].…”
mentioning
confidence: 99%
“…Apart from this type of variation, only the p.Val162 single-amino-acid in-frame deletion has been consistently associated with iron overload phenotypes. The p.Gly468Ser substitution can be considered separately, in that the underlying c.1402G>A transition disrupts the exon 7 donor site, resulting in the partial use of an exonic cryptic splice site and the generation of a truncated reading frame [27,28], while the Gly468 to Ser amino acid change by itself has no obvious effect on the ability of SLC40A1 to export iron [27].…”
mentioning
confidence: 99%
“…[ 7 9 ] It is assumed that the phenotypes of patients with SLC40A1 mutations vary depending on the mutation. [ 10 ] Mutations leading to ferroportin that is either not present normally at the cell surface or has defective iron export activity (loss of function) are associated with iron deposition in Kupffer cells and low transferrin saturation, [ 10 ] and define type 4A. Those mutated ferroportin that cannot be internalized after hepcidin binding (gain of function) are associated with iron deposition in hepatocytes and elevated transferrin saturation, [ 10 ] and define type 4B.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Mutations leading to ferroportin that is either not present normally at the cell surface or has defective iron export activity (loss of function) are associated with iron deposition in Kupffer cells and low transferrin saturation, [ 10 ] and define type 4A. Those mutated ferroportin that cannot be internalized after hepcidin binding (gain of function) are associated with iron deposition in hepatocytes and elevated transferrin saturation, [ 10 ] and define type 4B. A systemic meta-analysis of 176 individuals reported that SLC40A1 mutations, namely, V162del, D157N, D181V, G80V, Q182H, and R489K, may impair ferroportin's iron export function, and are common mutations for type 4A HH.…”
Section: Discussionmentioning
confidence: 99%
“…However, further functional studies or larger population studies are required to unequivocally link these variants to impaired ferroportin function and iron overload in individuals carrying these variants. The other six SLC40A1 variants identified in the ExAC data set (c.-59_-45del, p.Ile180Thr, p.Gly204Ser, p.Gly267Asp, p.Arg371Gln, and p.Gly468Ser) have all been associated with iron overload in patients and/or families, [26][27][28][29][30][31][32][33] although ferroportin containing the p.Ile180Thr variant seemed to behave similarly to the wild type when analyzed in functional assays. 30 The SLC40A1 p.Val162del variant has been reported as a cause of ferroportin disease more frequently (in nine publications) than any other SLC40A1 mutation (Supplementary Table S1 online); however, we did not detect it in any of the genomic sequence databases.…”
Section: Discussionmentioning
confidence: 99%